Emergency Contraception in Women of Slums in Northern India - Sonia Puri; N K Goe; Alka Sehgal; Dinesh Walia; Chetna Mangat (Tehran University of Medical Sciences, 2009)
Objective: To ascertain the utilization of the emergency contraception and to evaluate the impact of intervention on acceptability and utilization of emergency contraceptive pills. Materials and Methods: This community based cross sectional study was carried out by the department of community medicine in the slums of Chandigarh. The study sample was chosen by two stage systematic sampling. Participants were assessed regarding emergency contraception utilization and its various aspects and was also imparted correct knowledge regarding this mode of contraception. The women were reassessed again after six months to see the impact of the knowledge imparted to them on utilization of emergency contraception. Results: The study comprised of 1448, females and maximum were in the age group 26-35 years i.e. 717 (49.5%) followed by those in age group 19-25 yr i.e. 485 (33.5%). Considering their education, 674 (46.5%) women were illiterate. Only, 1.4% respondents had ever used emergency contraception. Sources of information so enumerated of emergency contraception were, health workers (0.8%), friends (0.6%), doctors/ health physicians (0.4%) media (0.3%) and books (0.1%). None of the respondent knew about the correct time span during which they should be used. The increase in utilization of emergency contraception from 1.4% to 4.2% was noticed in reassessment after 6months. Conclusion: Correct knowledge and awareness regarding emergency contraception can increase the utilization of it.